Brockton Public Library interior, staircase hall detail of stained glass, Brockton, Massachusetts. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
Interior detail of the staircase hall. Built in 1913. Library is located at 304 Main Street, Brockton, Massachusetts. (Source: Brockton Public Library website).; Caption on image: Library (9) SG Stairway hall 309 Main St.; Binder Number 4. Pocket Number: 8.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1970.; Apply to the DCA for access to the physical slides.